Building eCommerce applications (O'Reilly, 2011)
"This collection of articles and blog entries is representative of the full spectrum of commerce-related content we've published on PayPal's Developer Network over the past year. You will find tutorials and quick reference pieces for developers. With the creation of x.commerce we have expanded our coverage to address the needs of eBay and Magento developers and you can expect to see more content focused on helping both the developer and merchant communities in the coming year. Our team has covered a wide variety of topics including building mobile shopping carts, QR codes, working with various PayPal APIs, including how to integrate PayPal with other technologies such as WordPress. Three main themes have emerged in the commerce world today: mobile, social, and local."--Resource description page.